Empires and the acceleration of wealth inequality in the pre-Islamic Near East: an archaeological approach - Squitieri, Andrea; Altaweel, Mark (Archaeological and anthropological sciences, 2022)
We present an approach comparing wealth inequality between c. 3000 BCE and 224 CE in the Near East using house sizes and urban area from 1060 houses in 98 archaeological sites. We divide this dataset into two chronological phases, firstly c. 3000-800 BCE and secondly 800 BCE - 224 CE. The first phase is characterised by small, relatively weak states, while the second phase is characterised by major empires and large states, termed as the Age of Empire (AoE). For these two periods, inequality is measured using house size in relation to settlement scaling, and applying, in addition, the Gini and Atkinson indices on house sizes. Results demonstrate that pre-AoE houses have a lower scaling metric (β) that measures house size relative to site size (0.24), while for the AoE the value is higher (0.41). This indicates more rapid median house size expansion during the AoE as cities grew larger. For the pre-AoE, Gini and Atkinson inequality measures result in 0.45 and 0.16, respectively, while the AoE demonstrates 0.54 and 0.24 for the same measures, respectively. This demonstrates greater house size inequality in the AoE. Overall, we see that wealth inequality is not only greater in the AoE, but that increased wealth inequality has a likely power law relationship to increased settlement area. Alternative metrics to minimise data biases affecting results, including median house size and bootstrap sampling, are applied to strengthen these results and overall conclusions.
Gesehen am 17.10.2022